A Study on The Inner Mindsets of Entrepreneurs ~ somethings behind their successful careers ~ - Christy, Nisa Novia Avien; Slahanti, Masine; Basmar, Edwin; Wibowo, Radna Andi (Jurnal Economic Resource, 2024)
A successful enterprise in the contemporary economy requires appropriate skills and persons possessing an entrepreneurial mindset. The entrepreneurial mindset is crucial for achieving success in the company. The current degree of entrepreneurial mindsets within each group must be assessed by identifying the deficiencies that require modification to promote entrepreneurial success. This research examines successful entrepreneurs' inner mindset and characteristics and the variables contributing to their career achievements. The study's respondents consisted of four entrepreneurs from the Central Java region. The collected data were analysed following the seven steps of Interpretative Phenomenological Analysis (IPA) focusing on the participants’ life experiences and their inner mindset, motivations, behaviours, and successful career in their entrepreneurship process. This study demonstrates that the components of an entrepreneurial mindset—such as (1) generally request themselves to be a good model in their community; (2) always searching for any opportunity to open their business; (3) tend to see failure as a learning process and as a self-development enhancing event; (4) tend to see and further facilitate their team development and company goals; (5) generally possess the capacity for leadership and communication skills —are integral to the three dimensions of an entrepreneur's inner mindset, which facilitates of successful careers.